Control of Soil-Borne Disease of Soybean - Gretchen F. Sassenrath; Christopher R. Little; Xiaomao Lin; Sylvia R.G. Moraes (Kansas Agricultural Experiment Station Research Reports, 2023)
Soil-borne diseases are a significant cause of reduction in crop yield. Alternative management of soils can enhance the natural disease-controlling organisms in the soil. This study explores the impact of alternative production methods on a primary soybean disease, charcoal rot, caused by the fungusMacrophomina phaseolina. Treatments that could potentially enhance or control the disease were implemented, and soil tests were conducted for nutrient and disease presence. Manure increased the nutrient levels in the soil, as expected, but did not impact the disease control. Solarization increased the temperature within the plots, and increased the number of colony forming units ofM. phaseolina. Environmental conditions during the 2022 growing season were much hotter and drier than normal, leading to reduced soybean yields.
Keywords: soybean production; charcoal rot; Macrophomina phaseolina; soil health; soybean cyst nematode; suppressive soils